Analysis of donor deferrals causes in blood donation center-tertiary care hospital study - Duvvuri, P. Sindhur Rani; Teendra, Bharath; Pola, Neelima; Vasireddy, Guvera; Aparna, C.; Mayilanandan, Shusmitha; Sruthi, Yaddanapudi (International Journal of Research in Orthopaedics, 2024)
Background: Blood donor selection is important in providing safety to the recipients and also preventing transfusion related complications. Temporary causes for deferral should be counseled while permanent causes deferred for a life time. In this study, analysis was done to know the causes donor deferrals. Methods: A one year cross- sectional study was conducted in our hospital from the period March 2022 to March 2023.All the donors who were unfit for blood donation were included in the study. All the reasons for the deferrals are listed and analyzed the data. Results: Among 7147 total donations, voluntary are 3775, replacement are 3372.Out of which 150 donors are deferred, most were males 129 (86%) and the rest were females 21 (14%). The rejection rate in our study was 2.09%. The most common reason for the permanent rejection is Hepatitis-B and low hemoglobin level for temporary rejection. Conclusions: A vast majority of donors were rejected permanently 103 (68.6%), while the rest of them were rejected temporarily 47 (31.4%).